2020
DOI: 10.1080/1573062x.2020.1713171
|View full text |Cite
|
Sign up to set email alerts
|

Flash flood simulations for an Egyptian city - mitigation measures and impact of infiltration

Abstract: Flash flood simulations for an Egyptian city-mitigation measures and impact of infiltration Within this work, the impact of mitigation measures and infiltration on flash floods is investigated by using a 2D robust shallow water model including infiltration with the Green-Ampt model. The results show the combined effects of infiltration and mitigation measures as well as the effectiveness of bypass channels in addition to retention basins. Retention basins at appropriate locations could reduce the maximum water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It is a Java-based flexible and extendable modeling framework, which has been developed at the Chair of Water Resources Management and Modeling of Hydrosystems of the Technische Universität Berlin, Germany. Previous studies using hms have been carried out for example by Hassan et al [23], Özgen et al [49], Simons [62], and Tügel et al [69]. In hms, the depth-averaged 2D shallow water equations are solved with an explicit cell-centered finite volume method, and incorporates robust numerical methods such as the HLLC Riemann solver and a sophisticated total variation diminishing method (TVD) to deal with the numerical challenges, which are associated for example with the simulation of very small water depths over complex topography or the propagating wet-dry fronts [63].…”
Section: D Shallow Water Model For Overland Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a Java-based flexible and extendable modeling framework, which has been developed at the Chair of Water Resources Management and Modeling of Hydrosystems of the Technische Universität Berlin, Germany. Previous studies using hms have been carried out for example by Hassan et al [23], Özgen et al [49], Simons [62], and Tügel et al [69]. In hms, the depth-averaged 2D shallow water equations are solved with an explicit cell-centered finite volume method, and incorporates robust numerical methods such as the HLLC Riemann solver and a sophisticated total variation diminishing method (TVD) to deal with the numerical challenges, which are associated for example with the simulation of very small water depths over complex topography or the propagating wet-dry fronts [63].…”
Section: D Shallow Water Model For Overland Flowmentioning
confidence: 99%
“…[54] leads to a strong overestimation of infiltration, as the entire rainfall inside the domain and almost the whole incoming flood wave from the large wadi catchment completely infiltrated before reaching the city of El Gouna [69]. As there have been large flooding areas observed by the population -reported in personal conversations with shop owners and staff members of the desalination plant as well as reported through photographs of inundation areas and resulting damages -it is obvious, that the infiltration is not represented realistically.…”
Section: Case Study -Flash Flood Simulations In El Gouna Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…In hydrological operation, infiltration is the most important water loss during flash floods, and a good understanding of infiltration is crucial for an appropriate representation of runoff generation and losses [53]. Attempts to improve the infiltration process were made by previous studies [26,30,53,54]. Liu et al [26] modified the Green-Ampt equation in the MISDc model to improve flood simulation with fixed values of the maximum water capacity parameter (W_max) but the improvement was minuscule, where the evaluation index (NSE) increased from 0.71 to 0.73.…”
Section: The Importance Of W_max Parameter Estimation In Flood Simulamentioning
confidence: 99%
“…In previous work, a sensitivity analysis on a simplified catchment was carried out, and the results showed that in addition to other parameters, such as friction and rain intensity, infiltration has a strong influence on runoff at the outlet of the catchment (Tügel et al 2018). In Tügel et al (2020a), the impacts of infiltration under different parameter sets as well as under different mitigation measure scenarios for the city of El Gouna were studied, and infiltration was represented for different extreme rainfall events. As Hou et al (2020) showed that the temporal storm resolution plays an important role in obtaining reliable simulation results of inundated areas, a temporal rainfall distribution was incorporated in the model used to study flash floods in El Gouna instead of a simplified approach consisting of a constant average rain intensity, as used in earlier studies, e.g., Tügel et al (2020a).…”
Section: Introductionmentioning
confidence: 99%